2019
DOI: 10.1093/hropen/hoz004
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative live birth rates following a ‘freeze-all’ strategy: a population-based study

Abstract: STUDY QUESTION What is the cumulative live birth rate following a ‘freeze-all’ strategy compared with a ‘fresh-transfer’ strategy? SUMMARY ANSWER The ‘freeze-all’ strategy resulted in a similar cumulative live birth rate as the ‘fresh-transfer’ strategy among high responders (>15 oocytes retrieved) but did not benefit normal (10–15 oocytes) and suboptimal responders (<10 oocytes). WHAT IS KNOWN ALREADY Frozen-thawed embryo transfer is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
0
24
3
Order By: Relevance
“…In 1983, the first successful pregnant of frozen embryo transfer (FET) was reported in humans, and FET technology has been widely applied in the clinic ever since (1). FET use can reduce the risk of ovarian hyperstimulation syndrome (OHSS) and decrease the incidence of multiple pregnancies (2,3). In recent years, the development of cryopreservation technology has made the frozen-thawed embryo process safer.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, the first successful pregnant of frozen embryo transfer (FET) was reported in humans, and FET technology has been widely applied in the clinic ever since (1). FET use can reduce the risk of ovarian hyperstimulation syndrome (OHSS) and decrease the incidence of multiple pregnancies (2,3). In recent years, the development of cryopreservation technology has made the frozen-thawed embryo process safer.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between oocyte yield and the freeze-all strategy was reported in two population-based retrospective analyses [18,19]. However, these studies had heterogeneous patient populations in terms of the ages of the women and the stages of the embryos selected for transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative live birth rate per oocyte retrieval summarizes the chance of live birth during an entire treatment period [21,33]. To date, there have been only a limited number of randomized controlled studies (RCTs) compared cumulative live birth rate of 'freeze-all' versus 'fresh-transfer' strategy [34].The result of Li et al demonstrated that the cumulative live birth rate of 'freeze-all' strategy is similar as the 'fresh-transfer' strategy among high responders [35]. None of previous study has compared the cumulative live birth rate of high responders between different treatment protocols.…”
Section: Discussionmentioning
confidence: 99%